(untitled) (Journal of the College of Basic Education, 2022)
The original research in this topic revolves around the significance of the exclusive sentence on The concept, and to clarify this, we will talk about the restrictive sentence, and then about its concept. collection collection Exclusivity has multiple meanings, including: tightness, confinement, narrow-mindedness, and miserliness. And awareness of logic and prevention (1).